Social Stigma Against Patients with Infectious Diseases and Its Impact on Patient Mental Health (International Journal of Economics Management and Social Science, 2026)
Social stigma associated with infectious diseases represents a pervasive and damaging phenomenon that undermines the mental health and social wellbeing of affected patients. This study investigates the forms, mechanisms, and mental health consequences of disease-related stigma using a mixed-methods approach combining a structured survey (n = 285) with qualitative interviews among patients diagnosed with tuberculosis (TB), HIV/AIDS, and leprosy in three provincial hospitals in Eastern Indonesia. Quantitative analysis employing the Social Stigma Scale for Infectious Diseases (SSSID) and the Depression Anxiety Stress Scale-21 (DASS-21) revealed significant associations between experienced stigma and elevated levels of depression (r = 0.684, p < 0.001), anxiety (r = 0.651, p < 0.001), and social withdrawal (r = 0.712, p < 0.001). Logistic regression identified enacted stigma, self-stigma, and healthcare provider stigma as independent predictors of clinically significant mental health impairment. Qualitative themes illuminate the social dynamics of isolation, shame, and identity disruption experienced by patients. The findings call for integrating stigma-reduction strategies into infectious disease management protocols and advocate for a sociology-informed public health approach that addresses the structural roots of disease stigma.Keywords: social stigma; infectious disease; mental health; tuberculosis; HIV/AIDS; public health sociology; stigma reduction